2019
DOI: 10.1017/s0954579419000269
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate (variability) and the association between relational peer victimization and internalizing symptoms in elementary school children

Abstract: Relational victimization typically emerges first during the elementary school period, and has been associated with increased levels of internalizing symptoms in children. Individual differences in autonomic nervous system functioning have been suggested as a potential factor linking social stressors and internalizing symptoms. The aim of this study was therefore to examine whether heart rate and heart rate variability mediated the association between relational victimization and internalizing symptoms in 373 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Campus bullying cannot only cause depression in teenagers but it can also have a serious impact on their future social ability, learning ability, and academic performance . Bullying usually occurs in elementary school, a critical period in child development (Behnsen et al, 2020), and traditional bullying and cyberbullying victimization increase the likelihood of avoidance behaviors and of bringing a weapon to school (Keith, 2018). An alarming fact is that bullying can lead to antisocial behavior in adulthood (Stubbs-Richardson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campus bullying cannot only cause depression in teenagers but it can also have a serious impact on their future social ability, learning ability, and academic performance . Bullying usually occurs in elementary school, a critical period in child development (Behnsen et al, 2020), and traditional bullying and cyberbullying victimization increase the likelihood of avoidance behaviors and of bringing a weapon to school (Keith, 2018). An alarming fact is that bullying can lead to antisocial behavior in adulthood (Stubbs-Richardson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Olweus (1993a,b) pointed out that, often, students who bully others have a higher individual crime rate when they grow up, almost four times higher than others. In addition, victims of bullying are more likely to commit crimes in the future (Behnsen et al, 2020). Studies have shown that bullying victimization and perpetration correlate strongly and that their cross-lagged longitudinal relationship runs in both directions, meaning that perpetration is just as likely to lead to future victimization as victimization is to lead to future perpetration (Walters, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In exploring the mechanisms underlying this association, previous research has proposed that psychophysiological changes associated with the experience of maltreatment may link peer victimization to depression ( Teicher et al ., 2010 ; Teicher and Samson, 2013 ; Khan et al ., 2015 ). Consistently, psychophysiological links between peer victimization and depression have been reported ( Vaillancourt et al ., 2013 ; Mclaughlin et al ., 2014 ; Rudolph et al ., 2016 ; Erath et al ., 2018 ; Aults et al ., 2019 ; Lambe et al ., 2019 ; Behnsen et al ., 2020 ). More specifically, a distinct biological response pattern to social stressors induced by victimization in patients with major depressive disorder (MDD) has been posited ( Schiweck et al ., 2019 ; Iffland et al ., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk‐taking behaviors, such as aggressive or impulsive externalizing behaviors, have often been associated with lower resting or baseline heart rate (e.g., De Pascalis et al., 2007 ; Dietrich et al., 2007 ), while internalizing problems have been associated with higher heart rate (e.g., Behnsen et al., 2020 ; Byrne et al., 2010 ; Dietrich et al., 2007 ; Hastings et al., 2011 ). These findings might indicate that adolescents exhibiting higher risk‐taking may be hypo‐aroused, i.e., they may exhibit diminished physiological responses to stressors (Deutz et al., 2019 ; Hastings et al., 2011 ), and may therefore stimulate their arousal using risk‐taking behaviors.…”
Section: Introductionmentioning
confidence: 99%